Empowering application of basic life support management to cadre, District Astambul, Banjar Regency - Insana Maria; Annalia Wardhani (University of Merdeka Malang, 2025)
Cadres play a vital role in implementing health interventions within the community. Notably, 80 percent of emergency cases involving respiratory and cardiac arrest occur outside hospital settings. Cadres contribute significantly to building motivation and confidence in the management of Basic Life Support (BLS). This activity aimed to enhance the quality of health services by empowering community health cadres in BLS management. The method employed involved socialization and training provided to 22 community health cadres across villages in Astambul District. The results showed that 68 percent of cadres demonstrated a good level of knowledge following the socialization activities. The training outcomes indicated that 90 percent of cadres correctly performed the initial safety step (